Are Corporate Tax Burdens Racing to the Bottom in the European Union? - Signe Krogstrup (University of Copenhagen, Economic Policy Research Unit (EPRU), 2004)
This paper tests the central predictions of the theoretical tax competition literature for capital tax rates for a panel of European Union countries, notably a race to the bottom in corporate tax burdens. In contrast to the previous empirical literature, empirical support for increasing capital mobility to be resulting in a reduction in corporate tax burdens is found. The results also suggest that other factors driving the corporate tax burden should not be neglected and may provide substantial counterweight to tax competition forces
Keywords: H2; F2; F36; 330; Tax competition; Capital taxation; Corporate tax burden; European financial integration; Capital mobility; Steuerwettbewerb; Steuerbelastung; Kapitalertragsteuer; EU-Staaten